Pengaruh green supply chain management terhadap kinerja lingkungan dan ekonomi perusahaan pada peternakan ayam di Kabupaten Pesisir Selatan Sumatera Barat - Yalviolita, Cantika; Hendayani, Ratih (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The concept of Green Supply Chain Management (GSCM) is a strategic solution by companies or organizations in order to overcome this problem. The object of this study was the chicken farming industry in Pesisir Selatan Regency, West Sumatra. The aim of this study is that to determine how big the influence of Stakeholder Pressure, Green Supply Chain Management, company green resources on company performance (environmental and economic performance) on chicken farms in Pesisir Selatan Regency, West Sumatra Province. The method used in this study was a quantitative method. In order to obtain data, the researchers distributed questionnaires in the form of statements which represent previous study on chicken farming which includes all parts involved in chicken farming activities, both owners, workers, and final consumers. Moreover, the numbers of samples used were 100 respondents and the data analysis technique used was SEM-PLS using SmartPLS 3.2.9 and normality test using SPSS. Based on data analysis techniques which have been conducted by using SmartPLS, the result of this study shows that stakeholder pressure has a positive and significant impact on GSCM and the company's green resources. Meanwhile Green Supply Chain Management has a positive and significant impact on environmental performance and company economic performance.